A Pancancer Analysis of the Expression Landscape and Clinical Relevance of Fibroblast Growth Factor Receptor 2 in Human Cancers - Li, Juanni; Hu, Kuan; Huang, Jinzhou; Zhou, Lei; Yan, Yuanliang; Xu, Zhijie (Frontiers in Oncology, 2021)
Background: Fibroblast growth factor receptor 2 (FGFR2) is frequently altered in tumors and one of the top therapeutic targets in cholangiocarcinoma (CHOL) with FGFR2 fusions. Although there have been several studies on individual tumors, a comprehensive analysis of FGFR2 genetic aberrations and their simultaneous clinical implications across different tumors have not been reported. Methods: In this study, we used the large comprehensive datasets available, covering over ten thousand tumor samples across more than thirty cancer types, to analyze FGFR2 abnormal expression, methylation, alteration (mutations/fusions and amplification/deletion) and their clinical associations. Results: Alteration frequency, mutation location distribution, oncogenic effects, and therapeutic implications varied among different cancers. The overall mutation rate of FGFR2 is low in pancancer. CHOL had the highest mutation frequency, and fusion accounted for the major proportion. All these fusion aberrations in CHOL were targetable, and an FDA-approved drug was approved recently. Uterine corpus endometrial carcinoma (UCEC) had the highest number of FGFR2 mutations, and the most frequently mutated positions were S252W and N549K, where the functional impact was oncogenic, but targeted therapy was less effective. Additionally, DNA methylation was associated with FGFR2 expression in several cancers. Moreover, FGFG2 expression and genetic aberrations showed clinical associations with patient survival in several cancers, indicating their potential for application as new tumor markers and therapeutic targets. Conclusions: This study showed the full FGFR2 alteration spectrum and provided a broad molecular perspective of FGFR2 in a comprehensive manner, suggesting some new directions for clinical targeted therapy of cancers.